2011
DOI: 10.1093/jpepsy/jsr035
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence in Children with Chronic Illness: A Meta-analytic Review

Abstract: The impact of chronic illness on youth varied by individual child factors (e.g., gender, chronic illness type) and by measurement features such as informant and measure type. The current study demonstrates a need for further research of the assessment of social competence and has implications for the development of social skills programs for children with chronic illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
53
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 64 publications
8
53
0
3
Order By: Relevance
“…This may suggest that CSHCN status is associated with greater psychosocial demands than physical demands in this population. Review studies suggest that children with chronic health problems may have more difficulty adapting to psychosocial demands than healthy peers (49, 50). Third, in the known-groups validity analysis, the relative validity of the total scores was greater in the PedsQL, followed by KIDSCREEN-52, the CHIP, and the KINDL, suggesting that the PedsQL was the most sensitive in detecting differences between CSHCN and those without special health care needs.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that CSHCN status is associated with greater psychosocial demands than physical demands in this population. Review studies suggest that children with chronic health problems may have more difficulty adapting to psychosocial demands than healthy peers (49, 50). Third, in the known-groups validity analysis, the relative validity of the total scores was greater in the PedsQL, followed by KIDSCREEN-52, the CHIP, and the KINDL, suggesting that the PedsQL was the most sensitive in detecting differences between CSHCN and those without special health care needs.…”
Section: Discussionmentioning
confidence: 99%
“…The primary developmental outcomes examined are cognitive development and academic performance, emotional control and maturity, successful relationships with peers, and behavioral problems at home or at school (e.g., aggression, withdrawal). Numerous studies document strong and robust relationships between childhood chronic physical illness and developmental problems, especially poor cognitive/academic performance, problems developing relationships with peers, and low self-esteem (Forrest et al, 2011;Martinez et al, 2011;Pinquart, 2013;Pinquart and Shen, 2011). These problems tend to cumulate over time, leading to increasing developmental problems in adolescence (Verhoof et al, 2012).…”
Section: The Effects Of Health On Human Development: State Of the Evimentioning
confidence: 99%
“…Childhood mental illnesses also exact a severe developmental toll (Forrest et al, 2011;Martinez et al, 2011). Indeed, children with mental disorders appear to be at greater risk of stigma, bullying, and social isolation than those with physical illnesses (Walker et al, 2008).…”
Section: The Effects Of Health On Human Development: State Of the Evimentioning
confidence: 99%
“…15 Additionally, a meta-analysis reported that pediatric patients with neurological disorders, obesity, or blood disorders had significantly lower social self-competence than healthy comparisons. 16 Conversely, the same metaanalysis found that social self-competence was not significantly different from healthy comparisons in patients with asthma or diabetes. 16 Compared with normative samples, adolescents with musculoskeletal pain did not differ on multiple domains of perceived self-competence and had better perceived self-competence related to behavioral conduct.…”
mentioning
confidence: 95%
“…16 Conversely, the same metaanalysis found that social self-competence was not significantly different from healthy comparisons in patients with asthma or diabetes. 16 Compared with normative samples, adolescents with musculoskeletal pain did not differ on multiple domains of perceived self-competence and had better perceived self-competence related to behavioral conduct. 17 Considering the equivocal findings that emerge in the self-competence literature and the lack of research examining self-competence in pediatric patients with any type of cardiac condition, further research is needed to examine how this construct functions in children with pacemakers.…”
mentioning
confidence: 95%